2011
DOI: 10.1088/0067-0049/194/2/30
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Molecular Hydrogen in the Crab Nebula

Abstract: We have carried out a near-infrared, narrow-band imaging survey of the Crab Nebula, in the H 2 2.12 µm and Br 2.17 µm lines, using the Spartan Infrared camera on the SOAR Telescope. Over a 2.8'  5.1' area that encompasses about 2/3 of the full visible extent of the Crab, we detect 55 knots that emit strongly in the H 2 line. We catalog the observed properties of these knots. We show that they are in or next to the filaments that are seen in optical-passband emission lines. Comparison to HST [S II] and [O III… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 37 publications
4
33
0
1
Order By: Relevance
“…Grenman et al (2017) used Hubble Space Telescope optical images of the Crab Nebula to determine the extinctions of several dusty globules observed as dark spots against the synchrotron background, obtaining values of AV = 0.20−0.34. The globule sizes range from 6×10 15 cm to 3 × 10 16 cm, similar to the sizes of the H2 emitting knots observed by Loh et al (2011), although Grenman et al (2017) note that only ∼ 10% of their dusty globules are coincident with H2 knots. While the observed globule sizes are similar to our nH = 1900 cm −3 model cloud thicknesses, none of our preferred models match the extinctions found by Grenman et al (2017).…”
Section: Filament Size and Extinctionsupporting
confidence: 68%
See 4 more Smart Citations
“…Grenman et al (2017) used Hubble Space Telescope optical images of the Crab Nebula to determine the extinctions of several dusty globules observed as dark spots against the synchrotron background, obtaining values of AV = 0.20−0.34. The globule sizes range from 6×10 15 cm to 3 × 10 16 cm, similar to the sizes of the H2 emitting knots observed by Loh et al (2011), although Grenman et al (2017) note that only ∼ 10% of their dusty globules are coincident with H2 knots. While the observed globule sizes are similar to our nH = 1900 cm −3 model cloud thicknesses, none of our preferred models match the extinctions found by Grenman et al (2017).…”
Section: Filament Size and Extinctionsupporting
confidence: 68%
“…We list the surface brightnesses of emission lines observed in the Crab Nebula for each model in Table 5, along with observational upper and lower limits. Loh et al (2010Loh et al ( , 2011 observed emission from the H2 2.12 µm line from 55 knots in the Crab Nebula, with average surface brightnesses of ∼ 1 − 5 × 10 −5 erg cm −2 s −1 sr −1 . Figure 17 shows the surface brightness of this line versus ζ for our models, integrated up to AV = 3.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations